Motive of suffering in the works of Fyodor Dostoevsky (Eurasian Journal of Philology Science and Education, 2015)
In this article the main themes and issues of creation of Dostoevsky viewed through the prism of representations of Dostoevsky of human suffering, entailing a riot and humility. Suffering as a leading way to happiness –Dostoevsky felt himself suffering in prison. The author examines the philosophy of Dostoevsky which found artistic expression in his artistic texts. The fundamental basis of all of creation of Dostoevsky are suffering person who is not willing to put up with evil, urges to fight against it by moral ability . The article provides an analysis of disclosure ofthis theme in the novel of Dostoevsky «Humiliated and Insulted» («Униженные и оскорбленные»). In order to implement own idea writer throws his heroes into the abyss and checks human society according to the fair treatment of the weak.
Keywords: "an image of God"; suffering; "cleansing" mission of suffering; child’s tear